Rancang Bangun Alat Monitoring Penggunaan Air Pamsimas Berbasis Arduino Di Desa Sekartejo - Erman Al Hakim; Arba'i Yusuf; Rosyid, Muhail (JASATEC : Journal Students Of Automotive, Electronic and Computer, 2021)
The PAMSIMAS program is one of the government initiatives aimed at facilitating the water and sanitation needs of rural communities. One such PAMSIMAS program is implemented in the village of Sekartrjo, known as PAMSIMAS SEKAR TIRTA. The calculation of water prices and usage from PAMSIMAS is currently done manually, which is inefficient in terms of time and effort for the PAMSIMAS management. The objective of this research is to simplify the calculation of water prices and usage for PAMSIMAS management by creating an "Arduino-Based Water Usage Monitoring Device for PAMSIMAS." This research utilizes the Research and Development (R&D) methodology. The components used include Arduino UNO, an ultrasonic sensor HC-SR04, and an LCD display. The HC-SR04 sensor detects the water volume level released from the storage tank. When the sensor captures the signal waves, it adjusts the water flow distance set in the Arduino Uno Controller, and the calculation results are displayed on the LCD. It is expected that this product will assist the management of PAMSIMAS Sekar Tirta in the village of Sekartejo in effectively calculating volume and costs